2021
DOI: 10.1097/iae.0000000000003131
|View full text |Cite
|
Sign up to set email alerts
|

Late Presentation of Retinal Detachment

Abstract: Purpose: To describe and evaluate demographic, clinical features, prognostic factors, and rate of success of surgery and visual outcomes in patients with late presentation of retinal detachment. Methods: A retrospective, comparative, observational case series of patients with late presentation retinal detachment, defined as retinal detachment with the loss of central vision for 4 weeks or more, over a period of 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…First, there was a high rate of establish PVR at the time of the late recurrence-38% of cases. PVR is known to significantly influence surgical outcomes, with primary success rates between 43% and 69% 3,4 when there is established PVR. Second, the inability to detect the retinal breaks intraoperatively has been associated with lower primary success rates of 70% to 80%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there was a high rate of establish PVR at the time of the late recurrence-38% of cases. PVR is known to significantly influence surgical outcomes, with primary success rates between 43% and 69% 3,4 when there is established PVR. Second, the inability to detect the retinal breaks intraoperatively has been associated with lower primary success rates of 70% to 80%.…”
Section: Discussionmentioning
confidence: 99%
“…T he primary anatomical surgical success rate of noncomplex rhegmatogenous retinal detachment (RRD) has been reported between 72% and 93%; 1,2 however, it is less in PVR-associated RRD-43% to 69%. 3,4 Vitrectomy is currently the most common surgical technique for repair accounting for 79% and 83% of the cases in the United Kingdom and the United States, respectively. 5,6 In most clinical trials and series, the overall primary success rate is reported with a limited period of follow-up making it difficult to establish whether this success rate is maintained over the time and leaving open the questions of long-term success of retinal detachment surgery.…”
mentioning
confidence: 99%
“…This is in contrast to late presentation retinal detachment, which has commonly been described in low-income countries and attributed to a lack of access to healthcare, rurality and cost [ 3 ]. Recently, we have identified that late presentation retinal detachment (LPRD) continues to occur in the UK [ 4 ].…”
mentioning
confidence: 99%
“…We previously noted that LPRD does not appear to be related with socioeconomic or educational status [ 4 ]. Although cases can be treated with good anatomical results, there is a high incidence of proliferative vitreoretinopathy (PVR) and visual outcomes are often less favourable.…”
mentioning
confidence: 99%
See 1 more Smart Citation